Hilberträume einiger reproduzierenden Kerne und die Äquivalenz der Gaußschen Maßen - Mirskaja, T.; Pabedinskaitė, A.; Tempelman, A. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Т. И. Мирская, А. С. Пабединскайте, А. А. Темпельман. Гильбертовы пространства некоторых воспроизводящих ядер и эквивалентность гауссовских мерT. Mirskaja, A. Pabedinskaitė, A. Tempelman. Kai kurių reprodukuojančių branduolių Hilberto erdvės ir Gauso matų ekvivalentiškumas